Identity Formation of the Protagonist under Multicultural Influence in Mahdavi’s Ratu yang Bersujud - Ziana Fakhira; Raras Hafidha Sari (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study analyzes the process of identity formation of the main character through multicultural influences in the novel Ratu yang Bersujud by Mahdavi. The study was conducted through a literature study using descriptive qualitative data analysis techniques. The primary data sources used were novel text excerpts and secondary data came from formal objects in the form of data analysis and journal articles containing about the formation of women's identity and multiculturalism. The research population was the main character in the novel, while the data sample was determined through excerpts that describe the process of identity formation of the main character. The research instrument was the researcher herself with the help of a data recording sheet. The data analysis technique was carried out descriptively qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the multicultural context influences the process of identity formation of the main female character through four stages, namely confusion, negotiation, declaration, and reinforcement, which show that female identity is dynamic and formed through the interaction of cultural values, religion, and social experiences. These stages of the identity process become a means for the main character to reconstruct her identity amidst the pressures of a multicultural environment. These findings contribute to the study of literary psychology, particularly in understanding the dynamics of individual identity formation influenced by multicultural experiences in contemporary Indonesian literature.